The Effect of Basalt Material Composition and Rice Husk Ash on The Characterization of Paving Block - M Amin; Sudibyo Sudibyo; M Jannah; P Karo Karo (Journal of Engineering and Scientific Research, 2021)
Paving block (concrete brick) is a composition of building materials made from a mixture of Portland cement or other hydraulic adhesive. The making of paving blocks is done by a process of molding, soaking, physical testing including compressive strength, density, porosity, and absorption, and characterization including XRF and XRD. The paving blocks are made without the addition of basalt stone and rice husk ash and with the addition of 5%, 10%, 15%, 20% and 25% with a test life of 7 days, 14 days and 28 days. The materials used are cement, sand, basalt stone, rice husk ash and water. Paving blocks without the addition of basalt stone and rice husk ash have the highest compressive strength at the test age of 28 days of 9.9 MPa and absorption of 15.06%, whereas with the addition of basalt stone and rice husk ash the highest compressive strength is at a concentration of 5% at age 28day test of 12.25 MPa and the absorption value of 7.12%. The results of XRF characterization showed that the more concentrations of basalt stone and rice husk ash, the CaO contained in the paving blocks increased while the SiO2 decreased. The results of XRD characterization showed that the phases formed were ternesite, microline maximum and yeelimite.